The problem with women: a feminist interrogation of management textbooks. Issue 2 (3rd April 2019) - Williams, Kristin S.; Mills, Albert J.
ABSTRACT: Through an examination of management textbooks, beginning in 1950 and continuing to 2012, the authors chart the socio-political and historical context upon which the management texts were written and tease out the ways that women have been socially constructed as a problem to be managed . The study explores how the problem with women arose and how it has been maintained in organizational settings. The study undertakes a feminist interrogation to understand the systematic ways that roles and identities for women have been structured to both describe women negatively, limit and exclude them, and why such structures are durable. Additionally, the article asserts that the subtle shift from women as problem (collective), to a woman manager (as individual, as exceptional) and women as either the same or different from men, serves to blind us to the possibility of female governance.